2017
DOI: 10.1175/bams-d-16-0099.1
|View full text |Cite
|
Sign up to set email alerts
|

Over 5,000 Years of Ensemble Future Climate Simulations by 60-km Global and 20-km Regional Atmospheric Models

Abstract: An unprecedentedly large ensemble of climate simulations with a 60-km atmospheric general circulation model and dynamical downscaling with a 20-km regional climate model has been performed to obtain probabilistic future projections of low-frequency local-scale events. The climate of the latter half of the twentieth century, the climate 4 K warmer than the preindustrial climate, and the climate of the latter half of the twentieth century without historical trends associated with the anthropogenic effect are eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
308
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 377 publications
(356 citation statements)
references
References 38 publications
4
308
3
Order By: Relevance
“…Studies by [3][4][5] (Table S1) have revealed that the realistic reproduction of summertime precipitation over East Asia requires an atmospheric model with higher horizontal resolution. Therefore, we have been conducting a series of global warming projection experiments using the Meteorological Research Institute-Atmospheric General Circulation Model Version 3 (MRI-AGCM3) with 20-km and 60-km grid sizes [3,4,[6][7][8][9][10][11][12][13][14] (Table S1). These models have relatively higher horizontal resolution compared with global atmospheric models generally used in climate variability studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by [3][4][5] (Table S1) have revealed that the realistic reproduction of summertime precipitation over East Asia requires an atmospheric model with higher horizontal resolution. Therefore, we have been conducting a series of global warming projection experiments using the Meteorological Research Institute-Atmospheric General Circulation Model Version 3 (MRI-AGCM3) with 20-km and 60-km grid sizes [3,4,[6][7][8][9][10][11][12][13][14] (Table S1). These models have relatively higher horizontal resolution compared with global atmospheric models generally used in climate variability studies.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the uncertainty of precipitation over the southern part of Asia originates in the difference among cumulus convection schemes, while that over the Maritime Continent (MC) is caused by the difference among SSTs. The dependence of precipitation change on SST was further investigated using future SSTs obtained from the fifth phase of the Coupled Model Intercomparison Project (CMIP5) AOGCMs [11][12][13][14] (Table S1). However, the dependence of precipitation change on the cumulus convection scheme has not yet been fully examined using future SSTs of CMIP5 AOGCMs.…”
Section: Introductionmentioning
confidence: 99%
“…We described the experimental setup of the historical and the non-warming experiments of d4PDF, which is briefly explained in Mizuta et al (2016) and Kamae et al (2016). This is also the first study that has compared large-size longterm attribution experiments using two AGCMs, specifically MRI-AGCM3.2 and CAM5.1, to investigate the impacts of anthropogenic factors on historical changes in the frequencies of recordbreaking daily temperature and precipitation extreme indices.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The NW ensemble included SST data, excluding the first principal component mode of the historical SST change, which is similar to the linear trend pattern (i.e., we approximately removed the linear trends in SST). The SIC in the NW runs were estimated using an empirical quadratic relationship between SST-SIC (Hirahara et al 2014;Mizuta et al 2016). We used GHG concentrations, anthropogenic aerosol and volcanic sulfate aerosol values of 1850, and 1961 ozone concentrations.…”
Section: Experimental Setup and Extreme Indicesmentioning
confidence: 99%
“…If the number of the AGCM20km ensemble outputs is as many as the number of the AGCM60km outputs, such as more than 100 ensemble outputs from the database for Policy Decision making for Future climate change (d4PDF) experiments (Mizuta et al, 2016), the applicability of the model outputs in variant impact assessment research will be drastically increased.…”
Section: Introductionmentioning
confidence: 99%